2009
DOI: 10.1158/1078-0432.ccr-08-2984
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial of Darinaparsin in Patients with Refractory Solid Tumors

Abstract: Purpose: Darinaparsin, an organic arsenic, targets essential cell survival pathways. We determined the dose-limiting toxicity (DLT) and maximum tolerated dose of darinaparsin in patients with advanced cancer. (n = 3) resulted in no drug-related toxicities. Arsenic plasma levels peaked on treatment day 3, plateaued on day 5, and returned to baseline on day 7. Plasma levels varied within cohorts but increased with increasing doses. The median plasma arsenic half-life was 16.2 hours. Seven (17.5%) patients had st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The development of an oral form of darinaparsin and evidence of antitumor activity in phase I and II trials (6,18), together with the results of this study, provide a rationale for evaluating darinaparsin in patients with castrate-resistant prostate cancer. Xenograft studies with darinaparsin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The development of an oral form of darinaparsin and evidence of antitumor activity in phase I and II trials (6,18), together with the results of this study, provide a rationale for evaluating darinaparsin in patients with castrate-resistant prostate cancer. Xenograft studies with darinaparsin.…”
Section: Discussionmentioning
confidence: 98%
“…Phase I studies with darinaparsin in patients with advanced refractory solid tumors showed that 300 mg/m 2 i.v. for 5 consecutive days every 4 weeks was well tolerated (6). Phase II studies in both hematologic malignancies and solid cancers are currently under way (7,8).…”
Section: Introductionmentioning
confidence: 96%
“…Of 85 patients treated, 50 (59%) received single-agent targeted phase I therapy [15][16][17][18][19][20][21][22][23], 14 (16%) received a combination of targeted agents, 13 (15%) received chemotherapy combined with targeted agents [24,25], and eight (10%) received chemotherapy alone (Table 2) [26]. None of the patients was treated in a genotype-specific trial such as with anti-epidermal growth factor receptor (EGFR) therapy in patients with tumors harboring EGFR mutations or antianaplastic lymphoma kinase (ALK) therapy in tumors with EML4 -ALK fusion.…”
Section: Treatmentmentioning
confidence: 99%
“…4,5,79,80 Compared to IV ATO therapy, oral ATO has slower absorption resulting in reduced peak arsenic plasma concentration, which was found to be associated with lower levels of cardiotoxicity. 76,81 ATO induces apoptosis (cell death) and cell differentiation, inhibits proliferation and angiogenesis.…”
Section: 78mentioning
confidence: 99%
“…91 Arsenic trioxide and Darinaparsin are uptaken by different transport mechanisms, illicit somewhat differing protective responses, and they are metabolized by cells differently. 79,91,92 Darinaparsin was initially administered in IV (intravenous) form (no first-pass metabolism), but it is currently being evaluated as an orally administered medication. Current results show activity but as with all orally taken medications, first-pass metabolism could potentially limit its bioavailability.…”
mentioning
confidence: 99%